Iatrogenic Induced Complete Herniation of Vitreous - Atypical Presentation of Vitreous Touch Syndrome without Corneal Edema/ Decompensation in a Bilateral Aphakic Patient with Pseudoexfoliation Glaucoma - Prasanna Venkatesh Ramesh; Shruthy Vaishali Ramesh; Meena Kumari Ramesh; Ramesh Rajasekaran (Delhi Journal of Ophthalmology)
A 70-year-old female presented with blurring of vision and gush of warm fluid in the left eye (OS). She gave history of ocular surgery without lens implantation 20 years back in OS and five years back in the right eye (OD). On examination, visual acuity was hand movements in OS. The slit lamp examination revealed pseudoexfoliation with aphakia in both eyes with complete herniation of intact vitreous knuckle, bulging through the pupillary aperture and touching the corneal endothelium without corneal decompensation in OS and remnant posterior capsular rent in OD without vitreous disturbance.